THE INFLUENCE OF MOTIVATION AND PROMOTIONAL STRATEGIES ON MOTHER'S COMPLIANCE IN THE CONGENITAL HYPOTHYROID SCREENING PROGRAM AT TUMPANG HEALTH CENTER - Priyanti, Ida; Indasah, Indasah; Yenny Puspitasari (Bajang Institute, 2024)
Congenital hypothyroidism can cause long-term detrimental effects, the main of which is mental retardation. There is a need for examination of newborns to detect congenital hypothyroidism with Congenital Hypothyroid Screening (SHK) which is carried out with the aim of detecting congenital disorders as early as possible in babies. The aim of the research was to determine the factors that influence maternal compliance in the congenital hypothyroid screening program at the Tumpang Community Health Center. Observational research design with a cross-sectional approach. The population of all mothers with babies aged 0-28 days, was 135 respondents. The sample was 101 respondents with simple random sampling technique. Independent variables are motivation and promotional trategies. The dependent variable is mother’s compliance in the congenital hypothyroid screening program at Tumpang health center. The research instrument used a questionnaire that was carried out validity and reliability. The analysis used is univariate, bivariate, and multivariate analysis with logistic regression using SPSS 23. Research ethics Number: 001336/EC/KEPK/I/05/2024. The bivariate analysis carried out showed that there was a relationship between motivation factors and promotional strategies on maternal compliance with SHK, while the multivariate analysis showed that the most influential variable was the mother's motivation factor with a significance level of p=0.000. It is hoped that the results of the research conducted can serve as an appeal to mothers to comply with SHK procedures as an effort to improve their children's growth and development status.